Simulation of the effect of climate change on phenology and yield of dryland wheat in Kurdistan province - Fateme Aghamir; Saeid Soufizadeh; Ahmad Soheili (علوم محیطی)
Introduction: Climate change is one of the most important human challenges in food security in the agricultural sector, especially in arid and semi-arid regions. The most important climatic variables affecting crop yield, rainfall and temperature, carbon dioxide, especially in rainfed areas are of great importance. The results of researchers in Iran indicate the effect of obvious and undeniable climate change on crop yields in Iran. By using modeling knowledge in selecting the appropriate plant and cultivar for a region, determining the optimal plant characteristics, determining the best crop management, predicting the effect of diversity and climate change on crop growth and yield, and estimating potential yield in a low cost, fast and accurate way can be Adverse climate change on agriculture with negative mitigation options. Material and methods: In the present study, the effect of temperature increase, increase and decrease of 20% in precipitation and increase of carbon dioxide concentration on phenology and yield of dryland wheat in four cities of Dehgolan, Divandere, Saqez and Sanandaj in Kurdistan province with long-term climatic data of Kurdistan province in it was studied from 1370 to 1393. In this study, in order to simulate the daily growth and development of wheat in the conditions of climate change and to evaluate the potential effects of the simulation under the APSIM wheat model, 24 climate change scenarios and 1 baseline scenario, based on the product of temperature increase multiplied by +1, +2 , +3 and +4 ° C, change in precipitation of 2020% and three concentrations of carbon dioxide were considered 462.5, 527.5 and 725 ppm, respectively. Model inputs include climate (temperature, rainfall and radiation), soil (soil water and soil nitrogen), genetic coefficients and crop management information and its outputs including flowering date, physiological maturity date, maximum leaf area index date, leaf area index, Grain yield and biological yield were analyzed in future and past climatic conditions. Results and discussion: In scenarios with increasing rainfall compared to the base period, flowering uniformity, physiological maturity will increase in all cities but will decrease in Dehgolan. The uniformity of the maximum range of the leaf area index will increase in all cities and in Dehgolan the percentage of increase in uniformity is the lowest. Also, the uniformity of the leaf area index of Dehgolan and Sanandaj will increase, and Saqez and Divan Darreh will decrease. With decreasing rainfall, flowering uniformity, physiological maturity, the maximum range of leaf area index decreases in all cities and the percentage of uniformity reduction in Dehgolan is the lowest. With increasing rainfall, biological and grain yield fluctuations were highest in Dehgolan and lowest in Sanandaj, and with decreasing rainfall, all cities had biological fluctuations, Sanandaj had the least fluctuations and Divan Darreh had the most fluctuations. Conclusion: The effect of climate change factors including temperature, precipitation and carbon dioxide on different regions of Kurdistan province is different; In rainfed cultivation, in the basic period, wheat phenology and yield are affected by the initial water moisture in the soil, while by changing the climate, wheat phenology can be justified by increasing the temperature with the optimal crop temperature and by increasing rainfall with the wheat leaf area index.